BIODIVERSITY AND PLANT DISEASE MANAGEMENT: METHODS TO INCREASE THE RESISTANCE OF CORN (Eurasian Journal of Ecology, 2025)
Maize is one of the main crops that ensures global food security. To preserve maize biodiversity, it is necessary to combine traditional breeding methods with molecular genetics, expand seed banks and improve the skills of farmers. This will ensure food security and adaptation to climate change. To study the resistance of bladder wrack (Ustilago zeae) infestation and agronomic performance indicators in maize silage fields in 2023, a comprehensive analysis of 12 accessions was carried out. The results revealed significant differences in disease severity between accessions (p < 0.001), as well as a high heritability index of disease resistance (Hb² = 0.82). Plant height varied from 182 to 330 cm, among which the 4 tallest specimens stood out (Turan 680 SV, Turan 480 SV, Kazakhstan 700 SV, Kazakhstan 705 S0). The samples were divided into two groups according to the degree of resistance to Ustilago zeae: 5 samples had very slight damage (up to 1%) and 7 samples had slight damage (1–10%). The weight of 1000 grains was 226–330 g, the highest yield was noted in the varieties Altai 250 MV (330 g) and Budan 237 MV (310 g). The research results create a basis for improving corn breeding and developing effective methods for disease control.Keywords: corn biodiversity, resistance, 1000-kernel weight, grain yield, descriptive statistics